Middle Ear Histopathology Following Magnetic Delivery to the Cochlea of Prednisolone-loaded Iron Oxide Nanoparticles in Rats. (January 2018) - Lafond, Jean-Francois; Shimoji, Mika; Ramaswamy, Bharath; Shukoor, Mohammed I.; Malik, Pulkit; Shapiro, Benjamin; Depireux, Didier A.
Delivery of therapy to the cochlea is a challenge and limits the efficacy of therapies meant to treat hearing loss, reverse tinnitus, and protect hearing from chemotherapy regimens. Magnetic injection is a technique that uses magnetic fields to inject nanoparticles from the middle ear into the cochlea, where they can then elute therapy to treat hearing disorders. To evaluate the safety of this treatment in the middle ear, 30 rats were subdivided into 6 groups and treated by single or multiple intratympanic injections of saline, prednisolone, nanoparticles, or nanoparticles loaded with prednisolone. A specially designed magnet array was used to magnetically inject the particles from the middle ear to the cochlea. Treatment began at study day 0, and animals were euthanized on study day 2, 30, or 90. Temporal bones were collected and prepared for histopathological examination. Intratympanic administration of magnetic nanoparticles and/or prednisolone resulted in minimal to mild inflammatory changes in all treated groups. The incidence and severity of the inflammatory changes observed appeared slightly increased in animals administered nanoparticles, with or without prednisolone, when compared to animals administered prednisolone alone. At study day 90, there was partial reversibility of the findings noted at study day 2 and 30. Repeat administration did not appear to cause greater inflammatory changes.